Characteristics of Biostatic Body Indicators of Children of Senior Preschool Age with Various Body Postures - Bondar, Elena; Goncharova, Nataliya; Boyko, Anna; Бондар, Олена; Гончарова, Наталія; Бойко, Анна (Східноєвропейський національний університет ім. Лесі Українки, 2012)
Functional disorders of supporting-motor apparatus have an impact on the formation and physical development of the child’s body, which is especially important for children of the senior preschool age. The aim of the investigation: to study biostatic indicators of children of senior preschool age with different body postures. Research techniques: the analysis of specialist literature, pedagogical observation, anthropometric method, methods of estimating the localization of children’s common centre of gravity by graphic method and stability of children’s body, methods of mathematical statistics. Established that most children with posture, the most common of these is the posture in the frontal plane. Violation posture affect the stability of the body biostatychni performance of children who most clearly reflected in terms of the moment resistance of the body. Порушення функцій опорно-рухового апарату створюють вплив на становлення й фізичний розвиток організму дітей, що особливо актуально для дітей старшого дошкільного віку. Мета дослідження – вивчити біостатичні показники тіла дітей старшого дошкільного віку з різними типами постави. Методи дослідження: аналіз науково-методичної літератури, педагогічне спостереження, антропометрія, визначення локалізації загального центру ваги тіла дітей графічним методом та методи визначення стійкості тіла дітей, методи математичної статистики. Установлено, що більшість дітей мають порушення постави, найбільш поширеними з них є порушення постави у фронтальній площині. Порушення постави впливають на біостатичні показники стійкості тіла дітей, які найбільш наочно відбиваються на показниках моменту стійкості тіла.
Характеристика біостатичних показників тіла дітей старшого дошкільного віку з різними типами постави
Keywords: disorders of the supporting-motor apparatus; children of the senior preschool age; biostatic and goniometric indicators; порушення опорно-рухового апарату; діти старшого дошкільного віку; біостатичні й гоніометричні показники